Clonal interference of signaling mutations worsens prognosis in core-binding factor acute myeloid leukemia - Itzykson, Raphael; Duployez, Nicolas; Fasan, Annette; Decool, Gauthier; Marceau-Renaut, Alice; Meggendorfer, Manja; Jourdan, Eric; Petit, Arnaud; Lapillonne, Hélène; Micol, Jean-Baptiste; Cornillet-Lefebvre, Pascale; Ifrah, Norbert; et al. (Blood, 2018)
Mutations in receptor tyrosine kinase/RAS signaling pathway genes are frequent in core-binding factor (CBF) acute myeloid leukemias (AMLs), but their prognostic relevance is debated. A subset of CBF AML patients harbors several signaling gene mutations. Genotyping of colonies and of relapse samples indicates that these arise in independent clones, thus defining a process of clonal interference (or parallel evolution). Clonal interference is pervasive in cancers, but the mechanisms underlying this process remain unclear, and its prognostic impact remains unknown. We analyzed a cohort of 445 adult and pediatric patients with CBF AML treated with intensive chemotherapy and with deep sequencing of 6 signaling genes (KIT, NRAS, KRAS, FLT3, JAK2, CBL). A total of 152 (34%), 167 (38%), and 126 (28%) patients harbored no, a single, and multiple signaling clones (clonal interference), respectively. Clonal interference of signaling mutations was associated with older age (P = .004) and inv(16) subtype (P = .025) but not with white blood cell count or mutations in chromatin or cohesin genes. The median allele frequency of signaling mutations was 31% in patients with a single clone or clonal interference (P = .14). The repertoire of KIT, FLT3, and NRAS/KRAS variants differed between groups. Clonal interference did not affect complete remission rate or minimal residual disease after 1-2 courses, but it did convey inferior event-free survival (P < 10−4), whereas the presence of a single signaling clone did not (P = .44). This inferior outcome was independent of clinical parameters and of the presence of specific signaling clones. Our results suggest that specific clonal architectures can herald distinct prognoses in AML. •Presence of ≥2 independent subclones in the receptor tyrosine kinase/RAS pathway, defining clonal interference, is found in 28% of CBF AMLs.•Clonal interference predicts shorter event-free survival independently of clinical variables and presence of specific signaling mutations. [Display omitted]